Hubungan antara Kepuasan Kerja dengan Kinerja Tutor Paket C di PKBM Karang Taruna Kembang Delima - Oktavia, Gesri; Wisroni, Wisroni; Syuraini, Syuraini (Universitas Negeri Padang, 2018)
The background of this research is the low performance of Paket C tutor in PKBM Karang Taruna Kembang Delima. This is allegedly due to the low satisfaction of the tutor's work. The purpose of this research is to make the job satisfaction of tutor, to describe the performance of the package tutor, and to see the relationship of job satisfaction with the performance of the Paket C tutor in PKBM Karang Taruna Kembang Delima. This research is correlational research, with population is tutor of Paket C which amounted to 33 people, sample taken 90% from population that is 30 people with sampling technique that is simple random sampling. Data collection techniques used questionnaires, and data collection tools using questionnaires. Data analysis techniques to describe job satisfaction and performance tutor using the formula percentage, and to see the relationship of job satisfaction with the performance tutor technique data analysis using product moment correlation formula. The results of this study indicate that (1) the satisfaction of Paket C tutor in PKBM Karang Taruna Kembang Delima is low category, (2) the performance of tutor of Paket C package in PKBM Karang Taruna Kembang Delima category low, and (3) there is a significant relationship between job satisfaction with the performance of Paket C tutor in PKBM Karang Taruna Kembang Delima. It is suggested to the manager to improve the work satisfaction of tutors in terms of feelings of pleasure in work and a good working environment for the performance of tutors can increase.